Latest Miocene (Kapitean/Messinian) glauconite and the central Chatham Rise greensand: an enigmatic, highly condensed, relict/palimpsest deposit on the modern seafloor. Issue 4 (2nd October 2022) - Nelson, Campbell S.; Lawless, Anna S.; Nodder, Scott D.; Zwingmann, Horst
ABSTRACT: A unique 10–140 cm thick veneer of greensand and glauconite-rich deposits (10–80 wt% glauconite) presently sits atop central Chatham Rise (CR) in water depths of 200-500 m. The glauconite is dominated by chemically mature, polished ovoidal and lobate pellets, with a 10–12 Å phyllosilicate structure and K-Ar ages of 7–5 Ma, indicating that the glauconite pellets are predominantly allogenic (i.e. derived/reworked) grains, and not of in situ authigenic origin. Glauconite possibly evolved from seafloor alteration of detrital and/or volcanogenic smectitic clays, likely concentrated within organic-rich faecal pellets under unique paleoceanographic conditions (nutrient cycling, upwelling, carbon isotope gradients) within the latest Miocene Subtropical Front. The distribution of glauconite abundance suggests a 'glauconite factory' existed at this time about Reserve Bank on western central CR. The pellets were dispersed eastwards along the crest by intensified bottom currents within the dynamic Subtropical Frontal zone, perhaps during the numerous glacial periods of lowered sea level throughout the Plio-Quaternary. The bioturbated greensand veneer, and its mix of other reworked Neogene and Quaternary skeletal, phosphatic and siliciclastic components, rest unconformably on mainly Early Oligocene chalks, forming a highly condensed, relict/palimpsest deposit that alone embodies the last up to 30 My of sedimentation history atop central CR.